Situasi Politik Pemerintahan Dinasti Umayyah dan Abbasiyah - Munawir Haris (LPPM IAIN Sorong, 2018)
At the end of the Rasyidin Caliphate there was division within Muslims. Politically there are two dominant groups: Hasan bin Ali and Mu’awiyah bin Abi Sufyan. Politically there are two dominant groups, Hasan bin Ali and Mu’awiyah bin Abi Sufyan. After the negotiations, for the sake of unity of Muslims, it was agreed that Hasan acknowledged Mu’awiyah as the Caliph of the Muslim marked the emergence of the Umayyad Dynasty. The moment was called 'am jama'ah (unity year) in 661. The Abbasid Dynasty was the descendant of Prophet Muhammad's uncle, al-Abbas, who supported Ali bin Abi Talib and his descendants (including Hasan bin Ali). This paper aims to discuss some of the political situation that developed when the Umayyads (661-750) and the Abbasids (750- 1258). In Mu’awiyah bin Abi Sufyan's time there was a change of the political system from the khulafaur Rashidin into a system of al-Mulk (heredity monarchy) characterized by the appointment of his son, Yazin bin Mu'awiyah. This system adopted from the Persian and Byzantine kingdoms. However, maintaining the term caliph of Islam. Mu'awiyah also used Diwan and Sheikh to run the government, with the mechanism of Shura for consultative functions. After 150 years the Umayyads, the power was changed over by Abu al-Abbas Abdullah and marked the rising of the Abbasid in 750. In the Abbasid period the political and religious issues can’t be separated, which earlier in the Umayyad period were separated. The propaganda that the caliph is the representative of the people in carrying out God's command is valid until the Judgment Day. More explicitly, the term al-Imam (which also means the leader of prayer) is the leader in political affairs. In addition, the implementation of Islamic Shari'a is also more highlighted in governing the government and legitimating the power of the caliph. In general, the political style of the Abbasids is more Persian than the more Arab Umayyads